Facilitating police recording of the alcohol‐related characteristics of assault incidents: A stepped wedge implementation trial. (1st September 2015) - Wiggers, John H.; Hacker, Andrew; Kingsland, Melanie; Lecathelinais, Christophe; Tindall, Jennifer; Bowman, Jennifer A.; Wolfenden, Luke
Abstract: Introduction and Aims: Enforcement of liquor licensing laws is limited by inadequate police information systems. This study aimed to: (i) determine the effectiveness of an intervention in facilitating police recording of the alcohol consumption characteristics of people involved in assaults; and (ii) describe such characteristics by geographic area and setting of alcohol consumption. Design and Methods: A stepped wedge trial was conducted across New South Wales, Australia. An intervention to facilitate police recording of alcohol consumption information for people involved in incidents was implemented. For people involved in an assault the proportion for which alcohol consumption information was recorded was assessed. The proportion of assaults that were alcohol related, the proportions of people that consumed alcohol prior to the assault, were intoxicated, and had consumed alcohol in various settings, are described. Results: Post‐intervention, alcohol consumption information was recorded for 85–100% of people involved in an assault incident. The proportion of incidents recorded as alcohol‐related increased significantly (26–44.5%; P < 0.0001). The proportion of assaults classified as alcohol related was significantly greater in regional/rural areas (50–47%) than in metropolitan areas (38%). More people in metropolitan areas (54%) consumed alcohol on licensed premises prior to an assault than in regional/rural areas (39–42%), with approximately 70% of persons intoxicated regardless of setting of alcohol consumption. Twenty per cent of premises accounted for 60% of assaults linked to licensed premises. Discussion and Conclusions: The intervention was effective in enhancing the recording of alcohol‐related information for assault incidents. Such information could enhance targeted policing of liquor licensing laws. [Wiggers JH, Hacker A, Kingsland M, Lecathelinais C, Tindall J, Bowman JA, Wolfenden L. Facilitating police recording of the alcohol‐related characteristics of assault incidents: A stepped wedge implementation trial . Drug Alcohol Rev 2015;00:000–000]